Association of Antibiotic Rationality with Clinical Outcomes in Diabetic Foot Ulcer Patients in a Hospital in Badung, Bali - I Putu Yuda Pratama (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2025)
Type II Diabetes Mellitus (T2DM) patients are at high risk of systemic infections, such as Diabetic Foot Ulcer (DFU). The rationality of antibiotic use in Indonesia has not yet reached 100%, which negatively impacts clinical outcomes. This study aims to analyze the relationship between the rationality of antibiotic use and clinical outcomes in T2DM patients with DFU at Badung Bali Hospital from July to September 2024. The study design was cross-sectional, involving 153 respondents with inclusion criteria (patients diagnosed with T2DM with DFU January 2023-July 2024, received antidiabetics and antibiotics) and exclusion (received antibiotics <24 hours {outpatient}, <72 hours {inpatient}, moved to another health facility). The rationality of antibiotic use was assessed using the Gyssens method supplemented by the latest therapeutic guidelines, and then the percentage was calculated. The analysis of the relationship between rationality and clinical outcomes was tested using Kendall's Tau-b. The results of the Gyssens evaluation showed that 96.92% and 98.13% were irrational in the outpatient and inpatient settings, respectively. Clinical outcomes were improved by more than 60%. There was a significant relationship (p = 0.009; r = -0.290) in inpatients, but not in outpatients (p = 0.493; r = -0.065). The low rationality of antibiotic use in this finding can serve as a basis for practitioners to evaluate and prevent resistance and worsening conditions.